PREOVULATORY FOLLICLE DIAMETER AND SERUM ESTRADIOL-17β AT ESTRUS HAS NO RELATION WITH SUBSEQUENT ESTABLISHMENT OF PREGNANCY IN POSTPARTUM CYCLIC BUFFALO - PRAKASH, S; SELVARAJU, M; PALANISAMY, M; VISHA, P (The Indian Journal of Animal Reproduction, 2016)
Twelve postpartum cyclic buffalo were artificially inseminated (AI) at an interval of 24h during estrus. Ultrasonography was performed at first AI to assess the preovulatory follicle diameter and blood samples were collected at same time to measure serum estradiol-17β concentrations. Sonography-aided pregnancy diagnosis was carried out on day 28 post-AI. The study revealed that preovulatory follicle diameter (P, 9.44±0.19 vs. NP, 9.05±0.25 mm), as well as serum estradiol 17β (P, 14.59±0.93 vs. NP, 13.39±0.37 pg/ml) on the day of AI, had no relation (p>0.05) with subsequent pregnancy outcome in buffalo.
Keywords: Buffalo; Estradiol-17β; Pregnancy; Preovulatory follicle; Ultrasonography